Dampak Tren Budaya K-Pop Terhadap Perubahan Perilaku Sosial Mahasiswa Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sumatera Utara Medan - Winda Kustiawan; Muhammad Yazid; Mhd Darul Amin Sitorus (EduInovasi: Journal of Basic Educational Studies, 2025)
The purpose of this research is to examine the impact of K-Pop cultural trends on changes in social behavior of students of the Faculty of Da'wah and Communication, State Islamic University of North Sumatra. This research is a field study with a descriptive qualitative approach and also uses literature studies. The research informants consisted of students of the Faculty of Da'wah and Communication who are fans of Korean Culture and are directly involved with K-Popers activities. The results showed that K-Pop culture trends have a complex impact on changes in student social behavior. On the one hand, this trend promotes positive values such as solidarity, hard work, and multicultural understanding. However, on the other hand, this trend can also lead to lifestyle changes, social pressure, disruption of academic balance, and financial problems. Therefore, it is important for university students to adopt K-Pop culture wisely, considering its impact on their social, academic and personal lives. The results of this study are expected to be a contribution to the study of popular culture, especially with regard to the influence of foreign culture on students.